1994
DOI: 10.1007/bf00173419
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships reveal recombination among isolates of cauliflower mosaic virus

Abstract: Isolates of cauliflower mosaic virus (CaMV) differ in host range and symptomatology. Knowledge of their sequence relationships should assist in identifying nucleotide sequences responsible for isolate-specific characters. Complete nucleotide sequences of the DNAs of eight isolates of CaMV were aligned and the aligned sequences were used to analyze phylogenetic relationships by maximum likelihood, bootstrapped parsimony, and distance methods. Isolates found in North America clustered separately from those isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 44 publications
1
21
0
1
Order By: Relevance
“…Coupled to this is the risk of generating unique viruses through recombination between established virus populations and newly introduced viruses. Recombination has been well documented as a key strategy for generating diversity in both RNA and DNA viruses (2,8,21,25) and appears to contribute substantially to the level of genetic variation among BFDVs; we found evidence of recombination in all but one of the viral genomes analyzed in this study. The failure to detect any recombinant regions within the genome of the Zambian isolate taken from a wild blackcheeked lovebird further suggests that separate and unique southern African genotypes may exist.…”
Section: Discussionsupporting
confidence: 64%
“…Coupled to this is the risk of generating unique viruses through recombination between established virus populations and newly introduced viruses. Recombination has been well documented as a key strategy for generating diversity in both RNA and DNA viruses (2,8,21,25) and appears to contribute substantially to the level of genetic variation among BFDVs; we found evidence of recombination in all but one of the viral genomes analyzed in this study. The failure to detect any recombinant regions within the genome of the Zambian isolate taken from a wild blackcheeked lovebird further suggests that separate and unique southern African genotypes may exist.…”
Section: Discussionsupporting
confidence: 64%
“…We have attempted to detect recombinant isolates in several potyviruses. Our approach, inspired by that used by Chenault & Melcher (1994) on cauliflower mosaic virus, is based on the search for virus isolates showing different clustering properties in trees constructed using different short regions of their genomes. The results obtained may then be confirmed by various statistical means.…”
Section: Author For Correspondence: O Le Gallmentioning
confidence: 99%
“…Previous studies of other viruses also indicate the importance of recombinations observed in these studies that were predominantly between strains of a given virus species (Chenault and Melcher 1994;Gibbs et al 1995;Lai 1992;Revers et al 1996;Roossinck 1997;Simon and Bujarski 1994).…”
Section: Recombination Events Among Recently Identified Tomatoinfectimentioning
confidence: 83%